1991
DOI: 10.1148/radiology.178.2.1987602
|View full text |Cite
|
Sign up to set email alerts
|

Malignancy associated with chronic empyema: radiologic assessment.

Abstract: Radiologic findings of six cases of malignancy associated with chronic empyema 5-39 years in duration were reviewed. Pathologic examination confirmed three B-cell non-Hodgkin lymphomas, one round-cell sarcoma, one mesothelioma, and one adenocarcinoma. Retrospective findings on plain chest radiographs suggested the occurrence of malignancy: increased radiopacity in the thoracic cavity, soft-tissue bulgings and/or unsharpness of fat planes in the chest walls, destruction of bone near the empyema, and extensive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 0 publications
1
36
0
1
Order By: Relevance
“…An enhanced mass adjacent to empyema or nodular pleural thickening on a chest CT scan is suggestive of malignancy complicated with chronic empyema [14]. Watanabe et al reported two types of tumor fi ndings in the literature [7], mass formation type and scattered foci type, and radiological fi ndings in this case were compatible with the former.…”
Section: Discussionmentioning
confidence: 50%
“…An enhanced mass adjacent to empyema or nodular pleural thickening on a chest CT scan is suggestive of malignancy complicated with chronic empyema [14]. Watanabe et al reported two types of tumor fi ndings in the literature [7], mass formation type and scattered foci type, and radiological fi ndings in this case were compatible with the former.…”
Section: Discussionmentioning
confidence: 50%
“…However, the management of lung cancer complicated with a thoracic empyema in an older patient remains a challenge. A few cases of adenocarcinoma-associated empyema have been reported previously, but the origin of the adenocarcinoma remains unknown (7)(8)(9). Some chest radiographic findings, such as new air-fluid levels, destruction of bone, soft tissue bulges in the chest wall and increased dens- ity in the thoracic cavity, can be suspicious of malignancy (7,9).…”
Section: Discussionmentioning
confidence: 99%
“…A few cases of adenocarcinoma-associated empyema have been reported previously, but the origin of the adenocarcinoma remains unknown (7)(8)(9). Some chest radiographic findings, such as new air-fluid levels, destruction of bone, soft tissue bulges in the chest wall and increased dens- ity in the thoracic cavity, can be suspicious of malignancy (7,9). Further studies of the pleural fluid should be conducted, including erythrocyte/leukocyte counts, gram staining, cultures, and cytological examinations (5).…”
Section: Discussionmentioning
confidence: 99%
“…5 Nakatsuka et al 6 reported that 88% of PALs showed a diffuse proliferation of large B-cell type cells, making it difficult to distinguish PAL from other diseases by radiographic findings. A biopsy is needed to confirm the diagnosis.…”
Section: Discussionmentioning
confidence: 99%